Multiply the top equation by 6 and and the bottom equation by –5 and then add the equations is the correct answer.
Solution:
Given system of equations:
8x + 5y = –7 – – – – (1)
–7x + 6y = –4 – – – – (2)
Multiply top equation by 6 and and bottom equation by –5
(1) × 6 ⇒ 48x + 30y = –42
(2) × –5 ⇒ 35x – 30y = 20
Now add these two equations, we get
(48x + 30y) + (35x – 30y) = –42 + 20
48x + 35x + 30y – 30y = –42 + 20
83x = –20
The variable y is eliminated.
Therefore Multiply the top equation by 6 and and the bottom equation by –5 and then add the equations is the correct answer.